On Some Historical Aspects of Money Laundering in Russia and China - A. S. Poliychuk (Евразийская интеграция: экономика, право, политика, 2022)
Aim. In this article, the author seeks to analyze some of the characteristic features of various forms of money laundering in Russia and China, with reference to the chronicles of past centuries, starting from the moment this phenomenon arose, which later became widespread in both countries.Tasks. To realize the main aim, the author gradually solves logically interconnected tasks: firstly, to identify the oldest forms of legalization of illegal income in Russia and China; second, to trace the logic of evolutionary changes in money laundering in the historical practices of both countries; thirdly, compare the Russian and Chinese experience in the studied system of economic structural and functional ties.Methods. When writing the material, methods of chronological reconstruction, historical analogy, analysis and synthesis, comparative studies were used.Results. The author established that for the first time corruption mechanisms for the legalization of illegal income arose in China in the 4th century BC, while in Russia this practice is clearly traced only from the 15th century. The article shows that in China during the Tang Dynasty (VII–X century AD), money laundering methods demonstrated active development, and then reached a level critical for maintaining statehood in the era of the Opium Wars (XIX century), although they were subsequently partially leveled during the socialist period of Chinese statehood in the twentieth century. By analogy, the author considers the historical background of the evolution of money laundering mechanisms in our country in the era of feudal fragmentation, as well as tsarist and Soviet power. The article attempts to compare two historical paintings — Russia and China.Conclusion. The author concludes that the processes of legalizing illegal funds in Russia and China have similar features and are intensified in connection with the most important historical events, therefore, modern models of money laundering and countering this illegal activity have characteristic features formed by cultural experience in a particular country.